Day to Day Variability and Reliability of Blood Oxidative Stress Markers within a Four-Week Period in Healthy Young Men. (15th October 2014) - Goldfarb, A. H.; Garten, R. S.; Waller, J.; Labban, J. D.
Abstract : The present study aimed to determine the day to day variability and reliability of several blood oxidative stress markers at rest in a healthy young cohort over a four-week period. Twelve apparently healthy resistance trained males (24.6 ± 3.0 yrs) were tested over 7 visits within 4 weeks with at least 72 hrs between visits at the same time of day. Subjects rested 30 minutes prior to blood being obtained by vacutainer. Results . The highest IntraClass correlations (ICC's) were obtained for protein carbonyls (PC) and oxygen radical absorbance capacity (ORAC) (PC = 0.785 and ORAC = 0.780). Cronbach's α reliability score for PC was 0.967 and for ORAC was 0.961. The ICC's for GSH, GSSG, and the GSSG/TGH ratio ICC were 0.600, 0.573, and 0.570, respectively, with Cronbach's α being 0.913, 0.904, and 0.903, respectively. Xanthine oxidase ICC was 0.163 and Cronbach's α was 0.538. Conclusions . PC and ORAC demonstrated good to excellent reliability while glutathione factors had poor to excellent reliability. Xanthine oxidase showed poor reliability and high variability. These results suggest that the PC and ORAC markers were the most stable and reliable oxidative stress markers in blood and that daily changes across visits should be considered when interpreting resting blood oxidative stress markers.